Epidemiology of Taenia saginata taeniosis/cysticercosis: A systematic review of the distribution in West and Central Africa - Hendrickx, E.; Thomas, Lian F.; Dorny, P.; Bobić, B.; Braae, U.C.; Devleesschauwer, Brecht; Eichenberger, R.M.; Gabriël, S.; Saratsis, A.; Torgerson, Paul R.; Robertson, L.J.; Dermauw, Veronique (Springer, 2019)
Background The zoonotic tapeworm Taenia saginata, although causing only minor discomfort in humans, is responsible for considerable economic losses in the livestock sector due to condemnation or downgrading of infected beef carcasses. An overview of current knowledge on the distribution and prevalence of this parasite in West and Central Africa is lacking. Methods We conducted a systematic review, collecting information on published and grey literature about T. saginata taeniosis and bovine cysticercosis from 27 countries/territories in West and Central Africa, published between January 1st, 1990 and December 31st, 2017. Results The literature search retrieved 1672 records, of which 51 and 45 were retained for a qualitative and quantitative synthesis, respectively. Non-specified human taeniosis cases were described for Nigeria, Cameroon, Senegal, Burkina Faso, Democratic Republic Congo, Guinea, and Ivory Coast (seven out of 27 countries/territories), while T. saginata taeniosis specifically was only reported for Cameroon. Most prevalence estimates for taeniosis ranged between 0–11%, while three studies from Nigeria reported prevalence estimates ranging between 23–50%. None of the studies included molecular confirmation of the causative species. The presence of bovine cysticercosis was reported for Benin, Burkina Faso, Cameroon, Central African Republic, Chad, Democratic Republic Congo, Ghana, Guinea, Ivory Coast, Mali, Niger, Nigeria, Senegal, and Tristan da Cunha (14 out of 27 countries/territories). Prevalence estimates ranged between 0–29%. Conclusions Our systematic review has revealed that human taeniosis and bovine cysticercosis are seriously understudied in West and Central Africa. The high prevalence estimates of both conditions suggest an active dissemination of this parasite in the region, calling for a concerted One Health action from public health, veterinary health and food surveillance sectors.